PENGARUH PEMBERIAN REBUSANDAUN SELEDRI TERHADAP PENURUNAN TEKANAN DARAH PADA PASIENHIPERTENSI DI WILAYAH KERJA PUSKESMAS TALAGA JAYA - Abdul Wahab Pakaya; Fadli Syamsuddin (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Hypertension is a symptom of increased blood pressure that can affect other organs and this disease is one of the highest disease at this time. The purpose of this study to determine the effect of celery stew on blood pressure reduction in hypertensive patients in public health center working area of Telaga Jaya. This research type is quantitative research with Quasi Experimental design. The population in this study amounted to 20 people. Sampling technique is Accidental Sampling.The results showed that both systolic and diastolic blood pressure there was a decrease after stewing of celery leaves for 7 consecutive days. Statistical test results obtained P <0.05. So it can be concluded there is influence of celery leaves stew towards blood pressure reduction on hypertension patient in public health center working area of Telaga Jaya.